2014
DOI: 10.3748/wjg.v20.i25.8102
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and thyroid dysfunction: A systematic review

Abstract: Thyroid hormones are totally involved in the regulation of body weight, lipid metabolism, and insulin resistance. Therefore it is anticipated that thyroid hormones may have a role in the pathogenesis of non alcoholic fatty liver disease (NAFLD) and non alcoholic steatohepatitis (NASH). In this study, we reviewed the current literature on the association between thyroid dysfunction and NAFLD/NASH. A search for English language medical literature reporting an association between thyroid dysfunction and NAFLD/NAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
106
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 66 publications
4
106
0
16
Order By: Relevance
“…Based on our findings, we suggested hormone disturbance as an important underlying driving force of NAFLD pathogenesis instead of the special diet. Previous studies also suggested that TH, estrogen, and GH were related to NAFLD and played roles in regulation of hepatic steatosis [16,46,54]. The results of these studies supported the present study in that they demonstrated the important role of hormones regulation in development of NAFLD.…”
Section: Discussionsupporting
confidence: 81%
“…Based on our findings, we suggested hormone disturbance as an important underlying driving force of NAFLD pathogenesis instead of the special diet. Previous studies also suggested that TH, estrogen, and GH were related to NAFLD and played roles in regulation of hepatic steatosis [16,46,54]. The results of these studies supported the present study in that they demonstrated the important role of hormones regulation in development of NAFLD.…”
Section: Discussionsupporting
confidence: 81%
“…This indicates that hypothyroidism may directly result in NAFLD irrespective of other metabolic risk factors. Considering the results of these studies, hypothyroidism may be added to risk factors of NAFLD (28). The findings of our study were correlated with a study done by Chung et al who concluded that subclinical hypothyroidism, even in the range of upper normal TSH levels, was found to be related to NAFLD in a dosedependent manner.…”
Section: Discussionsupporting
confidence: 80%
“…However, NAFLD patients were more likely to have low TSH levels although hypothyroidism and hyperthyroidism were not associated with NAFLD. The observed changes in TSH and free T3 levels may attribute to alterations in thyroid hormones due to sick euthyroid syndrome in NAFLD (28,43).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there were a 40% increased risk of NAFLD in individuals with TSH between 2.5-4.5 mIU/L compared to individuals with TSH lower than 2.5 mIU/L, which still yield more controversy regarding the never-ending discussion of whether to treat or not subclinical hypothyroidism. A systematic review found a 15.2% to 36.3% prevalence of hypothyroidism in patients with NAFLD/NASH and concluded that hypothyroidism should be added to risk factors of NAFLD/NASH (18). What remains to be known is if hypothyroidism predicts or not the severity of fatty liver disease, since different studies yielded controversial results (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…A systematic review found a 15.2% to 36.3% prevalence of hypothyroidism in patients with NAFLD/NASH and concluded that hypothyroidism should be added to risk factors of NAFLD/NASH (18). What remains to be known is if hypothyroidism predicts or not the severity of fatty liver disease, since different studies yielded controversial results (17)(18)(19)(20). Interestingly, however, is the possible role of oxidative stress and mitochondrial dysfunction in the pathogenesis of NASH.…”
mentioning
confidence: 99%